The hospital sink drain microbiome as a melting pot for AMR transmission to nosocomial pathogens - Gregory E. McCallum; James P. J. Hall (npj Antimicrobials and Resistance)
Abstract The hospital sink drain microbiome can harbour opportunistic pathogens and antimicrobial resistance genes (ARGs). Aspects of this habitat, such as exposure to disinfectants, antibiotics, nutrients, and body fluids could exacerbate horizontal gene transfer of ARGs and clinically impactful pathogen resistance. Here, we explore features of the hospital sink drain that may favour ARG acquisition and transmission, highlight studies providing evidence of transfer, and consider strategies to mitigate these risks.